A novel protocol architecture for IoT : efficiency through data and functionality sharing across layers - Guimarães, Vinícius Galvão (2019)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica. Programa de Pós-Graduação em Engenharia Elétrica, 2019.